The effects of the COVID-19 pandemic on perceived stress among Romanian young adults: negative affect and avoidant coping as mediators - Leonti, Raluca Maria; Muntele-Hendreș , Daniela; Turliuc, Maria Nicoleta (Anales de Psicología / Annals of Psychology, 2024)
Background and objectives: Although young adults were considered to face a lower risk of severe coronavirus infection, they were at higher risk for adverse psychosocial effects. The aim of this study was to test the mediating roles of negative affect and avoidant coping, firstly in the relationship between COVID-19 impact and perceived stress, and then in the relationship between perceived coronavirus threat and perceived stress. Design: Cross-sectional design. Methods: We conducted the study on a sample of 669 university students (aged between 18-28), during the critical fourth wave, when the delta variant was the dominant strain. Results: The results indicate significant positive associations between the impact of COVID-19 and perceived stress (r = .485; p < .001), and between perceived coronavirus threat and perceived stress (r = .283; p< .001). Our findings demonstrate that negative affect and avoidant coping serially mediate these relationships (total indirect effect = .3349, 95% CI, [.2858; .3852] / (total indirect effect = .2072, 95% CI, [.1515; .2624]). Thus, the impact of COVID-19 (β = .137; 95% CI [.0019; .0045]) and perceived coronavirus threat (β = .069; 95% CI [.0007; .0046]) induce an increase in stress not only directly, but also indirectly, through amplified negative affect, which in turn increases the specific-oriented use of avoidant coping strategies. Conclusions: Our results highlighted some new explanatory relationships between variables that affect mental health during the COVID-19 pandemic.